Efektifitas Kelas Edukasi (KE) Menyusui terhadap Peningkatan Efikasi Diri Ibu Postpartum di Puskesmas Ulaweng Kabupaten Bone - Kasmiati Kasmiati (Pusat Riset dan Inovasi Nasional, 2024)
Lactation is an integral part of the reproductive process, providing infants with ideal and natural nourishment while serving as a biological and psychological foundation for growth. The type of research used by the researcher is quantitative research with a Quasi-Experimental method. The design employed in this study is a two-group pretest-posttest design. This research design examines the effectiveness of educational classes in the experimental group, using the control group as a comparison. The researcher conducted an initial observation (pretest), enabling the examination of changes occurring before and after the experiment (posttest). The study was conducted at the UPT Puskesmas Ulaweng from March to June 2023. The population in this study included all postpartum mothers within the operational area of UPT Puskesmas Ulaweng from March 21 to June 21, 2023. The sample consisted of a portion of the population selected to represent it. The sample size was 30 postpartum breastfeeding mothers (0–7 days postpartum) within the operational area of UPT Puskesmas Ulaweng, divided into 15 participants in the control group and 15 participants in the intervention group. The instruments used in this research included health education tools. The study's results, analyzed using simple linear regression correlation tests, revealed a significant value of ρ=0.000<0.05, indicating a relationship with an r-value of 0.776 or 77.6%. This suggests a strong relationship between education and knowledge